Comparison of the potencies of ginger (Zingiber officinale) and fennel (Foeniculum vulgare) in ameliorating dysmenorrhea pain: A systematic review - Vienda Leony Agustina; Siti Khaerunnisa; Sri Ratna Dwiningsih (Universitas Airlangga, 2023)
HIGHLIGHTS Dysmenorrhea pain could be reduced through various non-pharmacological treatments, including administration of ginger (Zingiber officinale) and Fennel (Foeniculum vulgare) which had been shown to significantly reduce the dysmenorrhea pain intensity. The dysmenorrhea pain intensity reduction due to the administration of the natural herbs was not as significant as compared to the ibuprofen or mefenamic acid administration. ABSTRACT Objective: We aimed to compare the effect of ginger and fennel herbs treatment in reducing dysmenorrhea pain intensity. Materials and Methods: We used a systematic review method employing the PRISMA chart. PubMed, Science Direct, Scopus, and EBSCO were searched which resulted in 418 compatible literature. Among the studies found, 13 works of literature that met the PICO inclusion criteria were included in this study. The study subjects involved women aged 15 to 25 years old who experienced dysmenorrhea, had normal or high BMI levels, consumed or did not consume oral contraceptive pills (OCP), and had normal menstrual cycles. Results: The results presented significant decreases in pain intensity in 11 studies, while the two others have shown otherwise. The two studies, with insignificant results, failed to determine the optimum dose to produce the desired analgesic effects. Conclusion: The administration of herbal ginger is considered more effective in reducing the intensity of dysmenorrhea pain.